2022
DOI: 10.3390/ijms23179638
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Ammonia Decomposition for Hydrogen Production over Carbon Films under Low-Temperature Plasma—In-Situ FTIR Studies

Abstract: Due to easy storage and transportation, liquid hydrogen carriers will play a significant role in diversifying the energy supply pathways by transporting hydrogen on a large scale. Thus, in this study, amorphous carbonaceous materials have been employed for hydrogen production via ammonia decomposition under non-thermal plasma (NTP) conditions. The adsorption and splitting of ammonia over carbons differing in the chemical structure of surface functional groups have been investigated by in situ spectral studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The IR spectral changes observed when exposing the carbon surface to the oxygen atmosphere at temperatures as high as 300 °C were described in our previous studies. 22,23,29 The infrared spectrum of the C des �the carbon sample outgassed at 600 °C (Figure 1a)�shows the presence of two main groups of signals sharp at ca. 1600 cm −1 and mutually overlapped in the range of 1100−1500 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectral changes observed when exposing the carbon surface to the oxygen atmosphere at temperatures as high as 300 °C were described in our previous studies. 22,23,29 The infrared spectrum of the C des �the carbon sample outgassed at 600 °C (Figure 1a)�shows the presence of two main groups of signals sharp at ca. 1600 cm −1 and mutually overlapped in the range of 1100−1500 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moszczyńska et al also reported a plasma power dependence for NH 3 decomposition over carbonaceous catalyst material. The authors show increased NH 3 conversion from 40% to ∼100% when the normalized power was increased from 150 to 900 W/m . Gorky et al investigated the effect of NH 3 decomposition on MgTiO 3 metal-based perovskites under cold plasma conditions.…”
Section: Plasma Catalysis For Hydrogen Generationmentioning
confidence: 95%
“…However, the temperature of the NTAP increased significantly by ∼200 K across the power range tested, which could have also influenced the reaction performance. 198 Moszczynśka et al 293 also reported a plasma power dependence for NH 3 decomposition over carbonaceous catalyst material. The authors show increased NH 3 conversion from 40% to ∼100% when the normalized power was increased from 150 to 900 W/m.…”
Section: Advancements and Currentmentioning
confidence: 97%
“…Carbon-assisted CO 2 conversion studies under NTP environment were carried out in a glow discharge reactor and in an IR-vacuum cell, as described previously 33,34 plugged into a vacuum line. The initial pressure of CO 2 was constant and equal to 0.38 torr.…”
Section: Materials Characterizationmentioning
confidence: 99%